2023
DOI: 10.3390/pr11020632
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Deep Compost Application in the Areas around Vineyard Tree Trunks on Selected Soil Chemical Properties and the Vegetative Growth of the Vine

Abstract: In the context of sustainability, viticulture will address issues related to soil fertility in the coming period. Greater attention will therefore be paid to replacing traditional manure-based fertilisers, such as farmyard manure, with new types of fertiliser in the form of composts, digestate, etc. Experience to date suggests that good-quality composts are not only a source of nutrients that the vines take from the soil each year, but also a source of organic matter. The application of compost and its subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…This was puzzling because frequently compost increases soil nitrogen content [ 24 , 25 , 47 ]. However, compost rarely does not significantly increase nitrogen concentration, so our results are not vastly different from others [ 12 , 23 ]. Green waste compost often increases soil K and P concentrations [ 24 26 ].…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…This was puzzling because frequently compost increases soil nitrogen content [ 24 , 25 , 47 ]. However, compost rarely does not significantly increase nitrogen concentration, so our results are not vastly different from others [ 12 , 23 ]. Green waste compost often increases soil K and P concentrations [ 24 26 ].…”
Section: Discussioncontrasting
confidence: 69%
“…In the greenhouse experiment, 3 weeks after compost application, abundance was slightly increased but only after 8 weeks did 10% compost significantly increase bacterial abundance. Other studies report an increase in microbial biomass, so it was surprising to see that bacterial abundance in the growth chamber experiments did not respond to 10% compost (Table 3 ) [ 23 , 24 ]. Bacterial diversity and richness also proved to be unpredictable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in an increase in leaf area and a corresponding increase in mineral and chemical content. The dry matter content increases in parallel with the increase in leaf area [22,27] The increase in leaf area can be explained by the increase in vegetative growth due to the increase in the length of the main branches, which leads to an increase in leaf area. Additionally, the increase in leaf area can be attributed to the role of humic materials in improving the physical and chemical conditions of the soil and increasing the supply of nutrients to the vines.…”
Section: Leaf Area (M 2 Vine -1 )mentioning
confidence: 99%
“…The results showed that the addition of organic nitrogen at a rate of 75% and the addition of one of the humic acids at a rate of 25% significantly increased the vegetative growth, achieving a significant increase in leaf area. Showed [22] the effect of the use of two types of organic fertilizer, CO compost and L20 (humic materials and organic carbon), on the vegetative growth of two grape varieties, Sauvignon Blanc and Pinot Gris, at two different locations. The results showed that the CO+L20 treatment achieved the highest significant superiority in branch length at a value of 12.5% and 13.2% for the first and second locations, respectively, compared to the control treatment.…”
Section: Introductionmentioning
confidence: 99%